(untitled) (Scientific journal of the Fergana State University, 2025)
The article provides opportunities for using computer technologies in teaching elements of probability theory and mathematical statistics. Methods for solving problems on hypergeometric distribution and combinatorics are also considered. The developed materials were tested in the educational process of 2nd year students of the "Applied Mathematics" department of Fergana State University and the effectiveness of their use was determined.